Fathers’ Behavior in Providing Reproductive Health Information to Male Adolescents in Surakarta: A Qualitative Study - Kusumaningrum, Tanjung Anitasari Indah; Kusumawati, Yuli; Purworini, Dian; Arifah, Izzatul; Athaya, Muhamad Rivandi; Setyawati, Anisa; Had, Fairus El; Kurniawati, Nurdika; Trijaya, Trijaya; Almayda, Mutiara Bahi; Brilliyanti, Aulia Suffah; Livia, Wardhatul (Jurnal Promosi Kesehatan Indonesia, 2025)
Background: Adolescent males generally demonstrate a lesser understanding of reproductive health compared to their female peers. Paternal involvement is crucial in addressing this disparity, as fathers are perceived as facilitators of more comfortable same-gender interactions. This research employed the Theory of Planned Behaviour and the Health Belief Model to analyse fathers' roles in disseminating reproductive health information to male adolescents.Method: A qualitative study was conducted in Surakarta between January and April 2025. Seventeen fathers of male adolescents, aged 10–19 years, served as the primary informants. They were selected via purposive sampling based on specific inclusion criteria: being married and having prior exposure to reproductive health materials. The exclusion criterion was non-local employment without a daily commute. Source triangulation involved an additional 17 wives and 19 adolescents. Data were collected through in-depth interviews and analysed using Colaizzi's method.Result : The majority of fathers educated their children on reproductive health, indicating positive attitudes and an understanding of its significance for adolescents. Wives significantly influenced fathers' perceptions and communication regarding this topic. Time constraints emerged as a key issue, with fathers expressing willingness to participate when their teenagers were available. It was found that the simultaneous availability of fathers and teenagers was necessary to foster closeness and effective communication.